2021
DOI: 10.1177/23779608211009514
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity in a Community of Nursing Colleagues

Abstract: Introduction Several concepts have been used to describe the qualities of communities of nursing colleagues. Nonetheless, few studies have shed light on nursing communities by drawing on the concept of solidarity. Objective To explore solidarity among a community of nursing colleagues. Methods A qualitative research design with a reflective life world approach was selected. This study reused data from a larger Norwegian empirical study. The data from the original study consisted of qualitative interviews and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Furthermore, having trusting relationships with colleagues has been shown to have a positive impact on job satisfaction for nurses as well as improve patient safety (Labrague et al., 2022). These relationships are built on having a common goal to take care of patients while also providing support for one another (Kristoffersen, 2021). Findings from this study highlighted how district nurses valued the trusting relationships they had with nursing colleagues from other services.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, having trusting relationships with colleagues has been shown to have a positive impact on job satisfaction for nurses as well as improve patient safety (Labrague et al., 2022). These relationships are built on having a common goal to take care of patients while also providing support for one another (Kristoffersen, 2021). Findings from this study highlighted how district nurses valued the trusting relationships they had with nursing colleagues from other services.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers found that colleague solidarity had a strong positive correlation (r = 0.56, p < 0.001) with nurses' job motivation. Kristoffersen (2021) explored solidarity among a community of 13 nursing colleagues. Two themes emerged from the data: Having indispensable relationships and encouraging a relative absence of sympathy.…”
Section: Introductionmentioning
confidence: 99%
“…According to Uslusoy and Alpar (2013), colleague solidarity contributes to the development of colleagues’ competence, increases the quality of their nursing practice, facilitates collaboration, and protects them from undesirable destructive behaviors. Cramm et al (2013), Dan et al (2018), Goktepe et al (2020), Kilic and Altuntas (2019), and Kristoffersen (2021) reported that colleague solidarity enhanced nurses’ effectiveness in providing care to patients, expanded their knowledge and skills and protected them from negative destructive behaviors. Cramm et al examined the relationship between organizational characteristics (hierarchical culture, communication, and leadership style) and employee solidarity of 313 nurses in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation